Influence of Bacillus thuringiensis application timing on population dynamics of gypsy moth in Mediterranean cork oak forests. Issue 3 (31st October 2019) - Mannu, Roberto; Cocco, Arturo; Luciano, Pietro; Lentini, Andrea
Abstract: BACKGROUND: The gypsy moth, Lymantria dispar, is one of the main pests of oak forests worldwide and causes extensive defoliation during its periodic outbreaks. In the Mediterranean region, control of gypsy moth populations in cork oak forests is based on application of Bacillus thuringiensis serovar kurstaki ( Btk ) formulations. This research investigated the effects of Btk applications carried out in two different population development phases on gypsy moth population dynamics. With this aim, temporal and spatial fluctuation patterns of L. dispar egg density were monitored in cork oak forests treated with Btk applications from 2004 to 2009 in Sardinia (Italy). RESULTS: Applications undertaken during the progradation and culmination phases protected the oak canopies equally in the year of application, leading to a similar decrease in pest population density in the following year. However, the medium‐term effectiveness of Btk differed between the two application timings, because only applications in the culmination phase caused a gradual decrease in L. dispar infestations throughout subsequent years. By contrast, when the application was undertaken during the progradation phase, population density increased again after 2–3 years. Moreover, Btk applications in the culmination phase reduced significantly the number of years in which gypsy moth density was damaging compared with those done in progradation. CONCLUSIONS: Our results indicate that Btk applications during the culmination phase were more effective than those in the progradation period, because application in the latter case did not suppress the population, but only postponed the outbreak peak by 2–3 years. © 2019 Society of Chemical Industry Abstract : Timing of Bacillus thuringiensis ( Btk ) applications appears fundamental for improving gypsy moth control in cork oak forests. This article shows sprayings done during the increase phase of population postponed outbreak, whereas applications done in the culmination phase were more effective.